Identifying the Catalytic Active Sites in Heteroatom‐Doped Graphene for the Oxygen Reduction Reaction. Issue 5 (15th July 2016) - Flyagina, I. S.; Hughes, K. J.; Mielczarek, D. C.; Ingham, D. B.; Pourkashanian, M.
Abstract: Density functional theory (DFT) calculations can be used to help elucidate the structures of active sites on the surface of fuel cell cathode catalysts, which are exceptionally difficult to identify by experimental techniques. The cathode catalysts were modeled in nitrogen‐, boron‐, sulfur‐, and phosphorus‐doped graphene basal planes. Dually‐doped graphene structures combining nitrogen with phosphorus or sulfur are also studied. Potential energy profiles were obtained, and the energies and activation barriers of molecular oxygen binding to the doped graphene model structures were estimated in order to identify potentially active sites for the oxygen reduction reaction in fuel cells. Among the investigated doped graphene structures, the active sites for molecular oxygen chemisorption are identified in graphene doped with either two nitrogen, or two phosphorus, or one sulfur and one phosphorus atoms. Further, the analysis of atomic spin densities and charges in the model structures enables the correlation of the catalytic activity with electron density distribution.